Internet non-use: a comparative study of Great Britain and Sweden - Reisdorf, B; Bianca Christin Reisdorf (2013)
Digital inequalities continue to concern researchers across highly technologised countries. In recent years, however, most research on digital inequalities has focused on distinguishing different patterns of Internet use rather than examining Internet non-users. The few quantitative studies of non-use and reasons for non-use often stay on a descriptive level, while qualitative studies mostly investigate subpopulations, such as those living in specific neighbourhoods. Although there are a number of studies of digital inequalities among young people and the elderly, a systematic literature search finds no research focusing on middle-aged individuals, who might face specific problems with being offline, as they are of working age and more likely than other age groups to have children living in the household. On the basis of a mixed-methods research design that compares non-users in Great Britain and Sweden, the overarching research question for this study sheds light on the mechanisms contributing to Internet non-use, as it examines the socio-economic backgrounds, attitudes, perceptions, and everyday life experiences of non-users with a focus on 25 to 55 year-olds. It applies advanced statistical analyses of secondary nationally representative survey data as well as in-depth analysis of qualitative interviews with 10 middle-aged non-users from each country. The analysis of these combined data shows that while socio-economic variables still play an important role in influencing who is on- and offline, general attitudes towards technologies are even more influential. The study finds that there is a lack of life-fit (Selwyn 2006) of ICTs for a number of non-users and a potentially negative impact of warm experts (Bakardjeva 2005) who have previously been regarded as a positive influence. Moreover, vulnerable groups (e.g. immigrants) are facing more substantial problems, such as issues with literacy and language, which need to be tackled first. The deliberation of similarities and differences between Britain and Sweden against the backdrop of policy interventions and cultural values shows that being offline is not problematic for all Internet non-users; some of them thrive in highly technologised societies. The conclusion offers proposals for both future research and policy interventions for those, currently offline mainly due to socio-economic reasons, who would like to go online in the future.